Attitudes and practice patterns of Finnish obstetrician-gynecologists regarding patients' sexual problems - Aromaa, Anna (Elsevier, 2025)
Objective: Female sexual problems are common but are not routinely assessed in obstetrician-gynecologist appointments. Therefore, we evaluated obstetrician-gynecologists' attitudes and practice patterns regarding their patients' sexual problems.
Study design: A web-based questionnaire was used to collect information from each respondent on gender, age, education, occupational status, and the total number of patients treated per day and sexual issues dealt with per day.
Main outcome measures: This study covered three fields of interest: 1) attitudes toward sexual problems, 2) practice patterns in sexual history-taking, and 3) practice patterns in the treatment of sexual problems.
Results: Of the 328 respondents, 299 provided eligible responses (specialists, 83 %, n = 249; residents, 17 %, n = 50). Almost all obstetrician-gynecologists (95 %) considered treating sexual problems as an important health care practice, but only 45 % and 53 % asked about sexual problems and sexual life satisfaction during general medical history-taking, respectively. Most obstetrician-gynecologists (86 %) used open conversation to assess sexual history. Half (52 %) of them reported that diagnosing female sexual problems is difficult, with the female obstetrician-gynecologists (54 %) more likely to report difficulty than the male obstetrician-gynecologists (29 %). Of the obstetrician-gynecologists, 15 % prescribed medications, whereas 58 % prescribed other treatments. A third (34 %) received distinct instructions from their organization for referring patients to continued care.
Conclusions: Although almost all obstetrician-gynecologists reported that treating sexual problems is an important health care issue, fewer than half routinely inquired about sexual problems. The practice patterns regarding sexual problems were disorganized. Our results show a need for additional clinical practice guidelines and education in sexual medicine.